A relevância da afetividade na família e a responsabilidade civil do genitor por abandono afetivo - Corte, Karla Dalla (2024)
This article seeks to analyze the importance of affection within the family, as well as the possibility of holding the parent responsible in the face of emotional abandonment. The procedural method used was monographic, with a bibliographical research technique, and, as an approach method, hermeneutic. Initially, we sought to address the evolution of the family over time, which plays a significant role in the lives of children and adolescents. Secondly, there was a brief explanation of affection as a legal good and, also, of the suffering that the lack of it causes. That said, it is necessary to hold the parent responsible, since abandonment causes irreparable damage to the children.